Tocotrienol reverses nicotine-induced oxidative stress-related in vitro and in vivo embryonic development and pregnancy outcome in mice / Yuhaniza Shafinie Kamsani - Kamsani, Yuhaniza Shafinie (2014)
A study to evaluate the effects of nicotine and simultaneous supplementation of y-tocotrienol (y-TCT), one of the four isomers in tocotrienols (TCT), and nicotine, on in vitro and in vivo embryonic development in mice (Mus musculus) had been carried out. Several approaches were undertaken including an investigation on in vitro effects of various doses and durations of nicotine treatment on pre-implantation embryonic development. Results showed that nicotine treatment decreased the number of retrieved embryos, resulted embryo degeneration, delayed embryo cleavage, induced disproportionate size of blastomeres and degraded blastomeres (p<0.05). Moreover, the deleterious impact of nicotine on pre-implantation embryonic development was dose- and treatment duration-dependent with a corresponding increase in plasma malondialdehyde (MDA) concentrations (p<0.05). Based on this finding, the study was further elucidated in terms of examining the dose-related beneficial effects of y-TCT in nicotine-induced cessation of pre-implantation embryonic development in vitro. Results showed that y-TCT could prevent the duration- and dose-related deterioration of pre-implantation embryo quality when supplemented simultaneously with nicotine. Moreover, y-TCT of 60 mg/kg bw/day was found to be the optimal effective dose in lowering plasma levels of MDA during pre-implantation embryo development (p<0.05). Findings of in vitro study were applied in in vivo approach to evaluate the effect of simultaneous supplementation of y-TCT with nicotine on embryo development, blastocyst implantation, foetal growth, length of gestation, foetal outcome and survival rate of the neonates. Results showed that nicotine impaired post-implantation embryo growth and development (p<0.05). Pregnancy outcome and survival of the neonates were also reduced (p<0.05). The rise in oxidant levels reduced the enzymatic antioxidant defense system (p<0.05).< Pregnancy-related levels of progesterone (P₄) and oestrogen (E₂) were also significantly affected (p<0.05). Through combating nicotine-induced oxidative stress, y-TCT was able to sustain the physiological/normal sequence of blastocyst implantation, foetal growth, pregnancy outcome and survival of the neonates. Moreover, maintenance of pregnancy until term possibly resulted from sustaining the levels of plasma P₄ and E₂ as evident in normal pregnancy. In conclusion, y-TCT could be used to minimize nicotine-induced oxidative stress-related deterioration of pre- and post-implantation embryo development, intrauterine foetal growth, pregnancy outcome and survival of the neonates.